Maine Energy Planning Roadmap— Energizing Maine’s Future - Smith, Lisa; Marks, Jeff (Maine Policy Review, 2017)
This article describes the Maine Energy Planning Roadmap, which is scheduled for release in January 2018. The Maine Governor’s Energy Office (GEO), with the guidance of a diverse and accomplished steering committee and funding provided by the US Department of Energy (DOE), is developing the Roadmap.